Risk assessment of venous thromboembolism in medical patients - Harenberg, Job (Seminars in hematology, 2000)
Medical patients are at risk of venous thromboembolism (VTE). However, the extent of the risk is not well characterized. Risk stratification is an important part of effective thromboprophylactic management. The risks depend on the specific clinical risk factors in individual patients and include age, immobility, and prior history of VTE. Medical patient risk assessment models (RAMs) are not fully developed, but a number of specific risk factors have been characterized. Although at present prophylactic treatment is largely empirical, studies evaluating the effects of higher-dose regimens in at-risk patients are ongoing. Long-term prophylaxis may be of benefit to particular patient populations, including those with congenital and acquired aberrations in hemostasis. Published studies of low-molecular-weight heparins (LMWHs) show that these agents are at least as effective as low-dose unfractionated heparin (UFH), with a trend towards an improved safety profile. The results of ongoing studies will provide further insight into the risk of VTE in this important patient group.